A Study the review of Customer Perception on M- Commerce Adoption: Examining the Impact of Mobile Commerce Adoption on Customer Perception in India (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The term mobile commerce was first used in 1997 by Kevin Duffey to announce the GlobalMobile Commerce Forum. Mobile Commerce services are evolving rapidly due to the coming together ofmobile service providers, banks and payment service providers to offer more products and securetransactions through mobile networks. In recent years, diverse societal groups have begun to acceptmobile commerce more and more. Its expansion can be ascribed to demographic technological changesthat have impacted many facets of social cultural behavior in the modern world. In India, moreconsumers are switching to mobile commerce to achieve better and faster transactions thanks to theapplications' impressive growth. A significant portion of the Indian populace is being encouraged toadoption m-commerce by the introduction of low cost smart phones, high speed internet access, andfree internet services.